2021
DOI: 10.1080/15980316.2021.1941339
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual difference between the discomfort luminance level and the brightness of a head-mounted display (HMD)

Abstract: A psychophysical experiment was conducted to compare the discomfort luminance level and the brightness of a head-mounted display (HMD). The results showed that as the size of the HMD stimulus increased, both the discomfort luminance level of the HMD and the brightness of the HMD decreased, but the influence of the size change was more dramatic on the discomfort luminance level than on the brightness. This study showed that to provide a comfortable luminance level for HMDs, the adaptation luminance level and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Geometrical distortions (in position, shape, color, brightness, camera misalignment) induce visual fatigue (Bando et al, 2012;Gao et al, 2018;Xia et al, 2019;Hwang and Peli, 2020). Viewing angles can impact visual discomfort in HMDs (Iskander et al, 2019;Ha et al, 2021) Check for any geometrical distortion and correct it (Jones et al, 2015;Gao et al, 2018;Scarfe and Glennerster, 2019) VF_6 IV…”
Section: Optical Misalignment (Between Hmd Lenses and Eyes)mentioning
confidence: 99%
“…Geometrical distortions (in position, shape, color, brightness, camera misalignment) induce visual fatigue (Bando et al, 2012;Gao et al, 2018;Xia et al, 2019;Hwang and Peli, 2020). Viewing angles can impact visual discomfort in HMDs (Iskander et al, 2019;Ha et al, 2021) Check for any geometrical distortion and correct it (Jones et al, 2015;Gao et al, 2018;Scarfe and Glennerster, 2019) VF_6 IV…”
Section: Optical Misalignment (Between Hmd Lenses and Eyes)mentioning
confidence: 99%
“…It allows the virtual environment viewed with the HMD to appear brighter. When the HMD and LCD flat screens produced the same luminance, the HMD looked brighter than the LCD flat screens (Ha et al, 2021). Another study found that the 3D virtual reality scene with an HMD was perceived as brighter than the 2D scene with a luminance camera (Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%